Market Deficiencies: From Veblen to Akerlof and Shiller. Issue 4 (2nd October 2018) - Rutherford, Malcolm
Abstract: In the past, the standard discussions of market failures in economics textbooks confined themselves to issues involving externalities, public goods, and common property (open access). Subsequent to George Akerlof's famous article "The Market for 'Lemons, '" discussions of the problems created by asymmetric information gradually became standard fare, but the issues raised by thinking of asymmetric information in economic matters extend far beyond the used car and health insurance markets that are normally used as the paradigm cases. In fact, consideration of the problems of information will inevitably lead to an examination of the problems of market manipulation and fraud, especially in light of the 2008 financial crisis. Akerlof has travelled this path himself as indicated by his recent book with Robert Shiller, Phishing for Phools (2015). Akerlof and Shiller provide a litany of examples of manipulation and deception in advertising and in many markets including financial markets. They also have a chapter on "The Resistance and its Heroes" that highlights some of the people and agencies that have worked to expose and reduce phishing, but this chapter is remarkably sparse. What this article attempts to do is to fill out some of this history by focusing on the work of American institutional economists from Veblen to Galbraith, who critically examined the issues of manipulation and deception in advertising, salesmanship, and finance. Some general considerations relating to the problem of fraud are also discussed.